Ideological Inferences of Deictic Expressions in Mahamudu Bawumia’s 2024 Concession Speech - Ebenezer Asare; Benjamin Amoakohene; Victoria Ogunnike Faleke; Obed Atta-Asamoah (Journal of Pragmatics Research, 2026)
In Ghana’s evolving democratic landscape, concession speeches play a vital role in stabilising political emotions, legitimising electoral outcomes, and maintaining national unity. However, such speeches remain underexplored, particularly with regard to how deixis functions as an ideological and cognitive resource. This study, therefore, examines the types of deictic expressions and the ideological inferences embedded in Mahamudu Bawumia’s 2024 concession speech, focusing on how linguistic choices shape political meaning during electoral transitions. Adopting a qualitative, text-based approach, the study applies Critical Discourse Analysis by integrating van Dijk’s (1998) socio-cognitive model with Levinson’s (1983) deixis typology. The findings reveal that personal, social, temporal, and discourse deixis are strategically deployed to assert political maturity, reinforce democratic norms, construct group identity, and manage the relationship between the speaker and the audience. The analysis further demonstrates how deixis shapes public perception by framing the election outcome as legitimate and facilitating emotional transition from contestation to acceptance. The study advances scholarship on political discourse by demonstrating that deixis functions as an ideological resource in concession speeches, while also offering practical insights into how political communication can be used to manage legitimacy and emotional transition during periods of democratic change.